Two radio-emission mechanisms in PSR J0901-4624 - Raithel, C.; Shannon, Ryan; Johnston, S.; Kerr, M. (2015)
© 2015. The American Astronomical Society. All rights reserved. We have detected sporadic, bright, short-duration radio pulses from PSR J0901-4624. These pulses are emitted simultaneously with persistent, periodic emission that dominates the flux density when averaging over many periods of the pulsar. The bright pulses have energies that are consistent with a power-law distribution. The integrated profile of PSR J0901-4624 is highly polarized and shows four distinct components. The bright pulses appear to originate near the magnetic pole of the pulsar and have polarization properties unlike those of the underlying emission at the same pulse phase. We conclude that the bright pulses represent a secondary giant-micropulse emission process, possibly from a different region in the pulsar magnetosphere.